ANALISIS PENGARUH DIMENSI SERVQUAL TERHADAP KEPUASAN PELANGGAN BENGKEL ABADI SERVICE TAMBAHREJO - Nungky Kurnia Putri; Nurdin Nurdin; Tedi Rusman (FKIP Unila, 2016)
This study aimed to determine the effect of the dimensions of SERVQUAL (Service Quality) which covers the tangibles, reliability, responsiveness, assurance, and empathy for customer satisfaction of Bengkel